2010
DOI: 10.1007/s00266-010-9639-y
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Improvements of Skin Grafts in Nasal Tip Reconstruction

Abstract: Defect closure on the nasal tip subunit still remains challenging. Full-thickness skin transplantation still is used despite its poor outcome in terms of the nasal tip contour caused by lack of dermal tissue. To avoid subsidence deformities associated with nasal tip reconstruction with skin transplants, this study analyzed methods using combined epidermal and dermal replacement. For 30 consecutive patients with a nasal tip defect, a retrospective comparison was made between conventional full-thickness skin tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…We performed the first review of the literature about studies that describe dermal substitutes’ utilisation in reconstruction after skin tumour excision. Table enlists publications available until July 2017 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed the first review of the literature about studies that describe dermal substitutes’ utilisation in reconstruction after skin tumour excision. Table enlists publications available until July 2017 …”
Section: Discussionmentioning
confidence: 99%
“…NMSC present quite high recurrences' rates, and we evaluated their incidence in the studies reviewed. Of them, 25 did not report data about recurrence or did not provide the complete text in English in order to evaluate this aspect . Eleven studies showed no recurrences among their patients, while 6 articles reported cases of recurrence that ranged from 5% to 25% …”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study, Riml et al . [23] observed better outcome with a perichondrodermal composite graft and reported two patients developing fistulae after Matriderm ™ -aided skin transplantation. [23] We observed a complete graft take in three of four patients, but further studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Singh and Bartlett 20 modify the nasal subunit principle taking into account local characteristics such as skin color, texture, contour, and actinic damage. Esthetic considerations, such as skin texture, color, and contour, used in the resurfacing of skin defects have been chronicled in the evolution of nasal reconstruction 21 . Skin color, texture and contour play a critical role in final determination of the reconstruction type 22 .…”
Section: Aesthetic Characteristicsmentioning
confidence: 99%